Acute on chronic kidney disease in cats: Etiology, clinical and clinicopathologic findings, prognostic markers, and outcome. (22nd May 2020) - Chen, Hilla; Dunaevich, Asia; Apfelbaum, Naama; Kuzi, Sharon; Mazaki‐Tovi, Michal; Aroch, Itamar; Segev, Gilad
Abstract: Background: Chronic kidney disease (CKD) and acute decompensation of CKD (ACKD) are common in cats. Objectives: To characterize the etiology, clinical and clinicopathologic findings, and the short‐ and long‐term prognosis of feline ACKD. Animals: One hundred cats with ACKD. Methods: Retrospective study, search of medical records for cats with ACKD. Results: Common clinical signs included anorexia (85%), lethargy (60%), weight loss (39%), and vomiting (27%). Suspected etiologies included ureteral obstruction (11%), renal ischemia (9%), pyelonephritis (8%), others (6%), or unknown (66%). Hospitalization duration was longer in survivors versus nonsurvivors (median = 7 days, range = 2‐26 versus median = 3 days, range = 2‐20, respectively, P < .001). The survival rate to discharge was 58%. Age, serum creatinine, urea, and phosphorous concentrations were higher and venous blood pH was lower in nonsurvivors. However, only serum phosphorus remained associated with the short‐term outcome in the multivariable model ( P = .02; 95% confidence interval = 1.03‐1.39). Survivors had a median survival time of 66 days after discharge. Serum creatinine concentrations at presentation as well as at discharge were associated with long‐term survival ( P < .002 for both). Conclusions: The short‐term prognosis of ACKD is comparable to acute kidney injury, while the long‐term prognosis is guarded.